2020
DOI: 10.1371/journal.pone.0234327
|View full text |Cite
|
Sign up to set email alerts
|

Flower power in the city: Replacing roadside shrubs by wildflower meadows increases insect numbers and reduces maintenance costs

Abstract: Massive declines in insect biodiversity and biomass are reported from many regions and habitats. In urban areas, creation of native wildflower meadows is one option to support insects and reduce maintenance costs of urban green spaces. However, benefits for insect conservation may depend on previous land use, and the size and location of new wildflower meadows. We show effects of conversion of roadside plantings-from exotic shrubs into wildflower meadows-on (1) the abundance of 13 arthropod taxa-Opiliones,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 148 publications
(192 reference statements)
0
23
0
Order By: Relevance
“…Major roads can, thus, create a suitable habitat for shrub-dwelling orthopterans (especially ensiferans, such as Oecanthus pellucens, Pachytrachis gracilis, P. striolatus and Pholidoptera femorata, in this study) that would not be able to inhabit or would occur in much lower numbers in the surrounding grasslands [65]. Previous studies have suggested the potential of vegetated roadsides and railway verges as both supplementary habitats and refugia for Orthoptera in urban environments [33,78], but our results indicate that this could also be the case in (semi)natural landscapes, at least for certain functional groups. Most of the shrub-dwelling species recorded here are also omnivorous, their generalist feeding habits likely providing an additional advantage in a disturbed environment selecting against specialist herbivores [36].…”
Section: Road-associated Changes In Functional Trait Compositionmentioning
confidence: 65%
“…Major roads can, thus, create a suitable habitat for shrub-dwelling orthopterans (especially ensiferans, such as Oecanthus pellucens, Pachytrachis gracilis, P. striolatus and Pholidoptera femorata, in this study) that would not be able to inhabit or would occur in much lower numbers in the surrounding grasslands [65]. Previous studies have suggested the potential of vegetated roadsides and railway verges as both supplementary habitats and refugia for Orthoptera in urban environments [33,78], but our results indicate that this could also be the case in (semi)natural landscapes, at least for certain functional groups. Most of the shrub-dwelling species recorded here are also omnivorous, their generalist feeding habits likely providing an additional advantage in a disturbed environment selecting against specialist herbivores [36].…”
Section: Road-associated Changes In Functional Trait Compositionmentioning
confidence: 65%
“…In large part, this may be due to the reduced vegetation biomass and productivity per unit area in urban habitats where much of the landscape is impervious surface, such as cement or rooftops (Uhler et al, 2021). While studies that focus on local, green habitats in cities often find those habitats to be biological-diverse (Brunbjerg et al, 2018;Guénard et al, 2015;Mody et al, 2020;Theodorou et al, 2020;Turrini & Knop, 2015), such studies may risk missing the broader picture that the unsampled grey spaces of cities are likely to have low biomass, a reality reflected in our results from both Denmark and Germany.…”
Section: Discussionmentioning
confidence: 99%
“…This makes orthopterans reliable indicators of, for example, vegetation succession, overgrazing, eutrophication and changes in land management, both at the species and assemblage levels (Fartmann et al, 2012;Gardiner, 2018). A recent study has shown that the type of roadside vegetation (meadow vs. woody plants) affects orthopteran abundance (Mody et al, 2020), but no previous research has investigated spatial dynamics of orthopteran assemblages in relation to road-induced changes in vegetation cover and microclimatic factors.…”
Section: Introductionmentioning
confidence: 99%